If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 4 = 8x + -3 Reorder the terms: 4 + x = 8x + -3 Reorder the terms: 4 + x = -3 + 8x Solving 4 + x = -3 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 4 + x + -8x = -3 + 8x + -8x Combine like terms: x + -8x = -7x 4 + -7x = -3 + 8x + -8x Combine like terms: 8x + -8x = 0 4 + -7x = -3 + 0 4 + -7x = -3 Add '-4' to each side of the equation. 4 + -4 + -7x = -3 + -4 Combine like terms: 4 + -4 = 0 0 + -7x = -3 + -4 -7x = -3 + -4 Combine like terms: -3 + -4 = -7 -7x = -7 Divide each side by '-7'. x = 1 Simplifying x = 1
| 87-10a=100 | | -14.25+-3.78-(-5.78)-3.4= | | 2(x+2)+5x=6x+2 | | ln(5x+6)=2lnx | | ln(5x+6)=lnx | | 37=9x-8 | | 2x=5x+54 | | 24=6x-6 | | 29=4x+9 | | -2x+27=7x | | 5n-10=310 | | (9+21)*9=(10+x)*10 | | 18x^2-24xy+8y^2=0 | | 16=3x+10 | | 3p-2z= | | y=0.5+5 | | 81c^2+90c+25=0 | | 9*21=(10+x)*10 | | 3(3x-7)-2=3(x-4)+31 | | 4x^2-9x+16=2x+9 | | 2x(4-x^2)+12(x-1)=3(x-1)(2-x) | | 3(x+1)=8(x-2)+11 | | 5x+2=-2+2x+13 | | 7-8x=0 | | 6a=11a-15 | | 5x+4=10-4 | | 5x-(2x+4)=17 | | (6+4)*6=(5+x)*5 | | 8-1(x-y)=-3x+5 | | (x+5)+y=49 | | 20t-8t^2+12=0 | | 0.8-0.2x=0.2 |